The Analysis of Learning Outcomes through Problem-Based Learning Model Approach On Circle Materials - Muhamad Saleh, (Jurnal Serambi Ilmu, 2024)
Students still consider mathematics learning in school difficult. One of the factors causing this difficulty is because mathematics material is dominated by abstract material. The purpose of this research is: to determine the learningoutcomes of student learning outcomes through the application of the Problem Based Instruction Model. The selection of a learning model plays a large enough role to achieve educational goals. For that, we need a learning model that is able to increase student interest, motivation and learning outcomes. One learning model that can be used is Problem Based Instruction which emphasizes student activity. Problems in the learning process are directed to those related to everyday life so that students can immediately understand them. The populationin this study were all students of 8th grade totaling 50 students.The sample inthis study were students of 8th grade State Junior High School 14 Banda Aceh, as many as 25 students. This study used a Quasi-experimental approach with a one-shot case study design with quantitative research. Data collection was carried out using test instruments. The data processing technique is to use the ttest. The results showed that student learning outcomes in the material tangent to the inner and outer partnership of two circles of 8th grade State Junior HighSchool 14 Banda Aceh achieved student learning learning outcomes accordingto the Minimum Completeness Criteria (KKM) set by State Junior High School14 Banda Aceh.